Pengembangan Game Edukasi Geoworld Berbasis Virtual Reality Menggunakan Roblox pada Materi Geometri Kelas XII - Nabila Nasution; Syeila Fatiha; Mirna Sianipar; Syalwa Nur Alisya; Fevi Rahmawati Suwanto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Geometry is a branch of mathematics that requires strong visualization and spatial reasoning skills; however, its abstract concepts are often difficult for students to understand. The use of Roblox integrated with Virtual Reality (VR) technology offers a potential alternative for creating interactive learning experiences and facilitating a more concrete visualization of geometric concepts. This study aimed to develop GeoWorld, a Virtual Reality-based learning medium on the Roblox platform for Euclidean and non-Euclidean geometry, and to determine its validity and practicality. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 10 twelfth-grade science students at ATS-TSAQOFIY Islamic Boarding School. The research instruments included material expert validation sheets, media expert validation sheets, and student practicality questionnaires. The data were analyzed descriptively using validity and practicality percentage techniques. The results showed that GeoWorld achieved a material validation score of 89.00% and a media validation score of 82.00%, both categorized as very valid. In addition, the student practicality test resulted in a score of 74.80%, which was categorized as practical. These findings indicate that GeoWorld is feasible for use as a virtual reality-based mathematics learning medium, as it provides an interactive and engaging learning experience while helping students understand Euclidean and non-Euclidean geometry concepts more concretely.